2015
DOI: 10.1071/wf14034
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns in fire leverage: the response of annual area burnt to previous fire

Abstract: Prescribed fire is practiced around the world to reduce the effect of unplanned fire, but we hypothesise that its effectiveness is proportional to the mean annual area burnt by unplanned fire, which varies among biomes. Fire history mapping was obtained for six global case studies from a range of biomes:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 51 publications
2
44
5
1
Order By: Relevance
“…Leverage varies according to the annual extent of wildfire, extent of fuel treatment and the rate at which fuel loads recover (Price 2012). Leverage has been analysed on individual burns (Loehle 2004) and across landscapes (Boer et al 2009;Price et al 2012;Price et al 2015a). In a bioregional analysis of south-eastern Australia, Price et al (2015b) found no evidence of leverage within the study area's bioregion for the period 1970-2010.…”
Section: Discussionmentioning
confidence: 99%
“…Leverage varies according to the annual extent of wildfire, extent of fuel treatment and the rate at which fuel loads recover (Price 2012). Leverage has been analysed on individual burns (Loehle 2004) and across landscapes (Boer et al 2009;Price et al 2012;Price et al 2015a). In a bioregional analysis of south-eastern Australia, Price et al (2015b) found no evidence of leverage within the study area's bioregion for the period 1970-2010.…”
Section: Discussionmentioning
confidence: 99%
“…A similar increase in total area burnt due to prescribed burning is likely to occur in many regions globally (Price et al, 2015). However, this does not necessarily mean that the smoke impact is 3 times greater because less fuel is consumed in a prescribed fire.…”
Section: Introductionmentioning
confidence: 97%
“…Numerous recent fires in the western U.S. have been managed in part or in whole for ecological benefit (henceforth "restoration fires"), including over 12 fires in 2017 totaling more than 60,000 ha of burned area (Forest Service Fire and Aviation Management, personal communication). Both modeling and empirical studies support these actions by showing that wild and prescribed fires can limit growth and lower severity of future fires and losses (Collins et al 2009, Arkle et al 2012, North et al 2012, Houtman et al 2013, Hoff et al 2014, Parks et al 2014, 2015a, Price et al 2015 and facilitate suppression efforts (Moghaddas and Craggs 2007, Syphard et al 2011b, Cochrane et al 2012, Thompson et al 2016. However, despite these and other studies, including landscape simulation research in which alternative fire management studies are simulated over time Mladenoff 2007, Spies et al 2014), research is nonexistent on how landscape fire regimes and suppression budgets might change following long-term changes in fire policy.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that at some level of fire activity, fuels would begin limiting the growth of fires in subsequent years and reduce area burned and fire intensity because the consumption of fuels by wildfire would exceed accretion by forest growth and succession. We were specifically interested in evidence for tipping points (Adams 2013) and other discontinuities in fire feedbacks, and the overall leverage (Price et al 2015) of fire to reduce future fire. We also hypothesized that increased fire would lead to impacts on ecological values including habitat for species dependent on specific types of old growth forest.…”
Section: Introductionmentioning
confidence: 99%